Pengaruh Keamanan Data dan Kemudahan Penggunaan Terhadap Minat Menggunakan Aplikasi Bale by BTN Pada Masyarakat Kec. Medan Timur - Jani Putri Nasrani Br Karo-Karo; Natalia E.T. Sihombing; Darma Manalu (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2026)
The purpose of this study is to determine the effect of data security and ease of use on interest in using the BALE by BTN application among the community of Medan Timur District. The method used is a quantitative approach. Data were collected through questionnaires distributed to a sample of 100 respondents. The data analysis methods employed include instrument testing, classical assumption tests, and hypothesis testing using SPSS version 25. The results show that data security has a positive and significant effect on interest in using the application, as indicated by the t-value of the data security variable (X1), which is greater than the t-table value (2.297 > 1.984) with a significance level of 0.024 < 0.05. Ease of use also has a positive and significant effect on interest in using the application, as indicated by the t-value of the ease of use variable (X2), which is greater than the t-table value (3.964 > 1.984) with a significance level of 0.000 < 0.05. Simultaneously, data security and ease of use have a positive and significant effect on interest in using the application, as indicated by the F-value being greater than the F-table value (24.939 > 3.09) with a significance level of 0.000 < 0.05. The coefficient of determination (R²) is 0.340, meaning that data security and ease of use explain 34.0% of the variance in interest in using the application, while the remaining 66.0% is influenced by other variables not examined in this study.